2001
DOI: 10.1159/000046190
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Functional Partitioning of the Rabbit Digastric Muscle

Abstract: The rabbit digastric muscle has a single belly that opens and retracts the mandible. It does not contain connective tissue partitions, and all fibers arise from the same tendon and insert into a single broad site. Historically, it was assumed that the muscle functioned as a single unit. Since we had preliminary evidence that this might not be the case, we carried out five small studies in rabbits. First, we showed that electromyographic (EMG) activity varies between recording sites within the muscle during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Furthermore, the results agree with data found for the other masticatory muscles, 7,8,[21][22][23] and they confirm the heterogeneous activation capability as a general control behaviour for all masticatory muscles. This capacity does not exclude a homogeneous activation, 37 but it might be an additional control mechanism to meet the requirements for fine motor skills.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Furthermore, the results agree with data found for the other masticatory muscles, 7,8,[21][22][23] and they confirm the heterogeneous activation capability as a general control behaviour for all masticatory muscles. This capacity does not exclude a homogeneous activation, 37 but it might be an additional control mechanism to meet the requirements for fine motor skills.…”
Section: Discussionsupporting
confidence: 89%
“…[17][18][19][20] Thus far, the phenomenon of differential activation has been substantiated for the masseter, 8,21 the lateral pterygoid, 22 and the digastric muscles. 23 Evidence for the temporalis is conflicting, because the heterogeneous activation has been demonstrated by some groups, 7 but not by others. 24 The goal of this study was to investigate if a differential activation can also be detected for the medial pterygoid.…”
Section: Introductionmentioning
confidence: 99%
“…Tsuruyama et al 32 found three primary nerve branches that arose from the mylohyoid nerve in the digastric muscle of the rabbit. The most proximal branch (posterior) innervated the posterior region of the digastric.…”
Section: Discussionmentioning
confidence: 99%
“…While task unit differences are relatively common in the muscle system under study (34,55,56,62), it was surprising that different task units should have been activated in what is conventionally viewed simply as reflex emptying of the valleculae. Although the reflex pharyngeal swallow was largely isolated by the process of decerebration, we occasionally elicited additional rhythmic tongue and/or jaw activity.…”
Section: Nature Of the Emg Signalsmentioning
confidence: 99%